Comparison of Lumbar Kinematics with a History of Low Back Pain During Baseball Hitting - Oshikawa, Tomoki; Kaneoka, Koji; Morimoto, Yasuhiro; Akuzawa, Hiroshi (International Journal of Sports Medicine, 2020)
The purpose of this study was to examine the influence of a history of low back pain (LBP) on pelvic and lumbar kinematics during baseball hitting. Twenty collegiate male baseball players (age, 21±1 years; height, 172.8±4.7 cm; weight, 72.7±6.2 kg; baseball experience, 13±1 years) performed 5 bat swings. Participants were categorized into the LBP group (n=10) or control group (n=10) based on having experienced lumbar spine pain due to bat swing that lasted more than 24 h within the last 12 months. Three-dimensional kinematic data of the pelvis and lumbar spine during bat swing were measured. Two-way ANOVAs were used to compare pelvic and lumbar kinematics throughout the bat swing between groups, and independent t-tests were used to compare the other outcomes between groups. There was a significant main effect between groups in lumbar flexion angle throughout the bat swing (p=0.047). The mean lumbar flexion angle of the LBP group throughout the bat swing was less than that of the control group. Additionally, the peak angular velocity of lumbar flexion of the LBP group was significantly faster than that of control group (p=0.047). These results can be helpful for longitudinal studies that identify the risk factors of LBP due to bat swing.
Keywords: bat swing; kinematics; 3D motion analysis; lumbar spine